2012
DOI: 10.1371/journal.pone.0029982
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Medaka sox9 Orthologue Reveals a Conserved Role in Germ Cell Maintenance

Abstract: The sex determining gene is divergent among different animal species. However, sox9 is up-regulated in the male gonads in a number of species in which it is the essential regulator of testis determination. It is therefore often discussed that the sex determining gene-sox9 axis functions in several vertebrates. In our current study, we show that sox9b in the medaka (Oryzias latipes) is one of the orthologues of mammalian Sox9 at syntenic and expression levels. Medaka sox9b affects the organization of extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…Studies have shown that Sox9 plays critical roles in both ECM deposition and cell migration in various tissues and diseases (18). In the heart, Sox9 is required for proper organization the valvular ECM proteins (60), whereas in the gonads, Sox9 regulates many ECM proteins as well as modifiers of the ECM such as matrix metalloproteinases (61,62). Sox9 also plays a role in fibrotic and sclerotic disorders in various tissues, in which Sox9 causes excessive and inappropriate ECM deposition by activating ECM proteins (63)(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Sox9 plays critical roles in both ECM deposition and cell migration in various tissues and diseases (18). In the heart, Sox9 is required for proper organization the valvular ECM proteins (60), whereas in the gonads, Sox9 regulates many ECM proteins as well as modifiers of the ECM such as matrix metalloproteinases (61,62). Sox9 also plays a role in fibrotic and sclerotic disorders in various tissues, in which Sox9 causes excessive and inappropriate ECM deposition by activating ECM proteins (63)(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…We then asked whether the upregulation of Sdgc was due to the presence of a Y chromosome in germ cells or in somatic cells. To address this issue, we generated chimeric medaka by transplanting XY germ cells into XX hosts and vice versa (Nakamura et al, 2012b), using sox9b-DsRed/olvas-EGFP transgenic line as hosts and nontransgenic strains as donors. Prior to manipulation, the host germ cells with EGFP fluorescence were ablated by nanos3/cxcr4-morpholino injection.…”
Section: Expression Of Sdgc Depends On Y Chromosome Number In Germ Cellsmentioning
confidence: 99%
“…To eliminate the host's germ cells, 2000 ng/µl cxcr4-MO and 1000 ng/µl nanos3-MO were injected into one-or two-cell stage embryos (Kurokawa et al, 2006(Kurokawa et al, , 2007. The transplantation procedure was performed as previously described (Nakamura et al, 2012b).…”
Section: Chimeric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, our recent analysis indicated that sox9b − an orthologue of the mammalian Sox9 expressed in the supporting cells − is not directly involved in testicular differentiation. A study utilizing a medaka sox9b mutant demonstrated that the function of sox9b is more related to the maintenance of germ cells 51. The mutant also indicated that sox9b expression is more intense in the supporting cells surrounding the germline stem cell population than in those that surround the gametogenesis‐committed germ cells 24.…”
Section: Neofunctionalization Of Other Genes With Loss Of Germline Stmentioning
confidence: 99%